Peningkatan Kinerja Sumber Daya Manusia Berbasis Gaya Kepemimpinan, Kepercayaan dan Komitmen - Sumardona, Sumardona; Saida, Saida (Robust: Research of Business and Economics Studies, 2022)
The research examines and analyzes the effect of the variable leadership style on employee confidence, work commitments and human resources performance. Besides, this research examines and analyzes the influence of variables of trust employees to work commitments and tests and analyzes the effect of trust and commitment of employees working on the performance of human resources. This research was conducted by survey method by distributing questionnaires to 100 employees at the Regional Employment and Training Agency. Sampling using the census method to test the hypothesis using SEM with Partial Least Squares application program (PLS). The analysis showed that the style of leadership and a significant positive effect on employee confidence, work commitments and performance of human resources, and employee confidence and a significant positive effect on employee job commitment and confidence, while work commitments and a significant positive effect on the performance of human resources. Therefore, this research concludes that the leadership style is always friendly with subordinates, involving subordinates in decisions, and the importance of friends with common interests can increase the confidence of human resources, commitment to work and the performance of human resources. Besides, increased confidence and commitment to human resources work can improve the performance of human resources.